Niño quemado gran secuelado. Perfil clínico y calidad de vida - Llanos V. , Natalia; Yáñez D., verónica; Orellana S., Matías; Hidalgo G., Gabriela (Revista Hospital Clínico Universidad de Chile, 2013)
Burns are an important cause of morbidity in children. The medical advances in acute trauma care have led to an increase in the number of children with extense area of burned skin, whose sequelaes are cause of complications along their growth. Objective. To characterize population with over 25% of sequelae burn skin at the COANIQUEM Rehabilitation Center, Santiago. Additionally to measure their quality of life and suggest interventions to improve medical attention. Methods. Quantitative, non experimental, descriptive, comparative study. Results. A sample of 59 children were identified as having post-traumatic burned on morethan 25% of total body surface. 47% of them were men and 53% female. Most them (64%) were patients who lived outside the capital city, Santiago. 54% was burned during the ages between to 2 to 6 years old. 42% was burned with fire and 56% by scalding. Half the patients were admitted to rehabilitation before 2 month after injury. 64% has good adherence to treatment and a regular follow-up. A group of 29 KIDSCREEN-27 survey was analyzed. There were no significant differences between gender, age, residence or visibility scars. Conclusions. Epidemiology found in children with severe burn sequelae is consistent with findings from literature. Quality of life outcomes are similar to general population. The concept of pediatric major burn sequela is established for future research in this area.